2017
DOI: 10.1002/nau.23210
|View full text |Cite
|
Sign up to set email alerts
|

Could urinary nerve growth factor be a biomarker for overactive bladder? A meta-analysis

Abstract: A total of 17 published studies were included in this meta-analysis. Among the studies considered, patients with OAB had a significant higher baseline urinary NGF/Cr (NGF normalized to urine creatinine) level compared to those of controls (SMD = 0.74, 95%CI = 0.43-1.04, P < 0.00001). After treatment, the level of NGF/Cr decreased significantly in OAB group. However, there was no significant difference between patients with IC (interstitial cystitis)/PBS (painful bladder syndrome) and patients with overactive b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…There is considerable interest in new biochemical and imaging biomarkers that might replace detrusor overactivity as an objective clinical end point; however, none has progressed to widespread adoption in clinical practice. The most widely tested urinary marker, nerve growth factor, has demonstrated problems with specificity and reproducibility 170 . The most widely investigated imaging marker, bladder wall thickness, also failed to demonstrate prognostic value when tested in a large trial of implementation 171 .…”
Section: Discussionmentioning
confidence: 99%
“…There is considerable interest in new biochemical and imaging biomarkers that might replace detrusor overactivity as an objective clinical end point; however, none has progressed to widespread adoption in clinical practice. The most widely tested urinary marker, nerve growth factor, has demonstrated problems with specificity and reproducibility 170 . The most widely investigated imaging marker, bladder wall thickness, also failed to demonstrate prognostic value when tested in a large trial of implementation 171 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, the finding of the current study can correlate to women developing de novo urgency or frequency after mesh placement that opened the paravesical space. A couple of studies had demonstrated increased NGF levels on patients with overactive bladder and bladder inflammation 17,18 .…”
Section: Discussionmentioning
confidence: 99%
“…Because of its mitigating effects, menthol was a particularly interesting compound in the context of IC. Chronic inflammation is typical in the pathogenesis of IC 31 , and higher levels of pro-inflammatory cytokines, such as macrophage-derived chemokines 32 or urinary nerve growth factors, are reported to be associated with the disease 33 , 34 .…”
Section: Discussionmentioning
confidence: 99%